Risk assessment in investment project - A. L. Tkachenko; O. G. Sheveleva (Омский научный вестник: Серия "Общество. История. Современность", 2019)
The purpose of the study is to analyze the existing methods of assessing risk and uncertainty when making decisions about investing, to illustrate the application of one of the considered methods, the Monte-Carlo method, and to analyze the results obtained during the application of the method. The authors proposed the use of descriptive statistics to evaluate the results of investment risk simulation. As a result of the study, existing risk assessment and uncertainty methods are analyzed when deciding on investment, a Monte-Carlo simulation is performed using Microsoft Excel, and the results are analyzed using the Descriptive Statistics tool